Journaling to research the potentiality and acceptability of bringing a mindfulness-based intervention into a junior school to support pupil wellbeing - Crawford, Andrea (2022)
Research on mindfulness in education for supporting pupils’ mental health and wellbeing has predominantly focused on potential psychological and behavioural benefits. Broader, more philosophical issues regarding the purpose of its implementation and associated ethical dilemmas are neglected areas. Consequently, little research exists regarding the acceptability of mindfulness in schools. This qualitative study reports on the potentiality and acceptability of mindfulness taught via an MBI (mindfulness-based intervention) in a junior school. This study adds an extra critical dimension to the findings by exploring how the MBI is experienced by the recipients, i.e., teachers and pupils. It is an unusual aspect of research on mindfulness and education, as demonstrated by the notable lack of in-depth qualitative data offering such perspectives.